Urethra Sparing With Target Motion Mitigation in Dose-Escalated Extreme Hypofractionated Prostate Cancer Radiotherapy: 7-Year Results From a Phase II Study - Greco, Carlo; Pares, Oriol; Pimentel, Nuno; Louro, Vasco; Nunes, Beatriz; Kociolek, Justyna; Stroom, Joep; Vieira, Sandra; Mateus, Dalila; Cardoso, Maria Joao; Soares, Ana; Marques, Joao; et al. (Frontiers in Oncology, 2022)
Purpose: to explore whether the rectal distention-mediated technique, harnessing human physiology to achieve intra-fractional prostate motion mitigation, enables urethral sparing by inverse dose-painting, thus promoting dose escalation with extreme hypofractionated stereotactic ablative radiotherapy (SABR) in prostate cancer. Materials and Methods: Between June 2013 and December 2018, 444 patients received 5 x 9 Gy SABR over 5 consecutive days. Rectal distention-mediated SABR was employed via insertion of a 150 cm3 air-inflated endorectal balloon. A Foley catheter loaded with 3 beacon transponders was used for urethra visualization and online tracking. MRI-based planning using VMAT-IGRT with inverse dose-painting was employed in delivering the PTV dose and in sculpting exposure of organs at risk (OAR). A 2 mm margin was used for PTV expansion, reduced to 0 mm at the interface with critical OARs. All plans fulfilled Dmean ≥45Gy. Target motion ≥2mm/5sec motions mandated treatment interruption and target realignment prior to completion of planned dose delivery. Results: Patient compliance to the rectal distention-mediated immobilization protocol was excellent, achieving reproducible daily prostate localization at a patient-specific retropubic niche. On-line tracking recorded ≤1mm intra-fractional target deviations in 95% of treatment sessions, while target realignment in ≥2 mm deviations enabled treatment completion as scheduled in all cases. The cumulative incidence of late grade ≥2 GU and GI toxicities were 5.3% and 1.1%, respectively. The favorable toxicity profile was corroborated by patient reported QoL outcomes. Median PSA nadir by 5 years was 0.19 ng/mL. The cumulative incidence of biochemical failure using the Phoenix definition was 2%, 16.6% and 27.2% for the combined low/favorable-intermediate, unfavorable intermediate and high-risk categories, respectively. Patients with a PSA failure underwent a 68Ga-PSMA scan showing a 20.2% cumulative incidence of intraprostatic relapses in biopsy ISUP grade ≥3. Conclusion: the rectal distention-mediated technique is feasible and well-tolerated. Dose escalation to 45 Gy with urethral sparing results in excellent toxicity profiles and PSA relapse rates similar to those reported by other dose-escalated regimens. The existence of intraprostatic recurrences in patients with high-risk features confirms the notion of a high alpha/beta ratio in these phenotypes resulting in diminished effectiveness with hypofractionated dose-escalation.